Interpretasi Potensi Massa Longsoran Dengan Metoda Geolistrik(Studi Kasus Daerah Gayo Lues) - Muchlis Muchlis (Universitas Syiah Kuala, 2015)
One indication of a potential landslide area is a formation along the slip field slope. The slope is formed due to the difference between the cover layers (top soil) with a layer beneath it. The top layer is usually a layer of soil that passes the water so that it could be easily infiltrated into the slope. However, rain water infiltrated into the soil or are often not able to enter deeper into the ground because there is an impermeable layer which forms the slope area. Geoelectric resistivity method is generally used for shallow exploration, approximately to depth of 300 to 500 meter. The principle of the method is that the electrical current injected into the earth through two current electrodes, while the potential difference that occurs is measured through two potential electrodes. From the results of measurements of currents and electric potential difference can be obtained by variation of value of electrical resistivity in the layer below the measuring point. The resistivity value can show the bedding soils and on which one is the layer of slip field. From this study we expected the resistivity 2D cross section that shows the depth and dimensions of the field of slip on the slope studied so as to provide recommendations on the appropriate method of stabilizing slopes.